Scope and Difficulties of the Transmedia Practice. A Case Study on the Spanish PSM System - Larrondo Ureta, Ainara (Journalism practice, 2020)
According to a growing volume of academic literature on the subject, transmedia fiction and non-fiction production is now one of the main areas driving innovation in media companies, thanks to the improvements it brings in numerous interconnected fields: narrative and content, management and productive strategy, brand promotion, etc. In this context the article focuses on transmedia linked to public broadcasting companies, starting with a qualitative study based on interviews with expert professionals from thirteen corporations in Spain, one operating at the national level (RTVE) and twelve at the regional level (A Punt Media, CARTV, CCMA, CRTVG, CMM, EITB, EPRTVIB, RTVM, RTPA, RTVA, RTRM and RTVC). The results show how professionals view the concept of transmedia production, its advantages, disadvantages and the challenges it poses, which depend on these corporations' service and relationship with audiences. As the conclusions state, the keys factors for understanding the professional transmedia strategy of public broadcasting corporations are found in the characteristics of today's media market, which is suffering from budget cuts and growing competition.